Interactive E-Worksheets for Critical Thinking in Chemistry : A Three-Level Representation Approach to Voltaic Cells - Azizah, Alfina Norma; Dwiningsih, Kusumawati (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to investigate the impact of interactive electronic worksheets combining three chemical representation levels on students’ critical thinking skills in learning voltaic cells. This research utilises an R&D (Research and Development) method featuring a one-group pretest-posttest design. The participants in this study were 12th-grade high school students. The tools used in this research included validation sheets, pretest-posttest assessments, and feedback questionnaires. Validation data indicated that the e-worksheets were suitable for testing, achieving a median score of ≥ 4. The pretest-posttest results were analysed using the N-Gain score, which fell within the range of 0.7 to 0.9. Additionally, a paired t-test was conducted using the Minitab software, yielding a p-value of less than 0.05, signifying a meaningful enhancement in students’ critical thinking skills. The feedback from students regarding this media resulted in a practicality rating of ≥ 61%. In summary, interactive e-worksheets based on the three levels of chemical representation have been demonstrated to improve students’ critical thinking skills.